An imidazolium ionic compound-supported palladium complex as an efficient catalyst for Suzuki–Miyaura reactions in aqueous media. Issue 92 (20th September 2016) - Zong, Yingxiao; Wang, Junke; He, Yubi; Yue, Guoren; Wang, Xicun; Pan, Yi
Abstract : A water soluble and efficient ionic compound-supported palladium complex was prepared. Abstract : A water soluble and efficient ionic compound-supported palladium complex was prepared. The structure and composition of the complex was characterized by FT-IR, NMR, ICP-OES and mass spectrometry. The complex exhibits high catalytic activity for Suzuki–Miyaura reactions in aqueous media. Moreover, the catalyst shows outstanding stability and reusability, and it can be recovered simply and effectively and reused six times without much activity decrease.